Pengaruh Lama Penyimpanan Semen Segar pada Media Simpan Coldbox terhadap Motilitas, Viabilitas Spermatozoa dan pH Semen Ayam Buras - Alfonsius Bria; Agustinus A. Dethan; Charles V. Lisnahan (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
The purpose of this study was to determine the effect of storage time for fresh semen on media ColdBox on the motility, viability of spermatozoa and semen pH of native chickens. This research was conducted in October 2020 at the Laboratory of the Faculty of Agriculture, University of Timor Kefamenanu, North Central Timor Regency (TTU). Chicken semen used in this study came from 10 male native chickens with an age range of 2-3 years or with a spur length of 2-3 cm. This is the basis for selecting male livestock to produce quality cement which will be used as research material. This research used an experimental laboratory with a completely randomized design (CRD), which consists of 4 treatments and three replications so that there are 12 experimental units, namely: R1:Storage fresh cement over time (0 hours), R2:Storage fresh cement during the period ( 2 hours), R3: Storage of fresh cement for time (4 hours), R4: Storage of fresh cement for time (6 hours). The variables used in this study were: spermatozoa motility, spermatozoa viability, semen pH. The data obtained were analyzed using the Duncan Test of Variety Analysis. By using statistical software packages for the social sciences (SPSS. 20). The results showed that the mean spermatozoa motility in treatments R1, R2, R3 and R4, respectively, were mass motility of 4 ± 0, 4 ± 0, 4 ± 0 and 3 ± 0.6. Individual motility is 80 ± 00, 80 ± 00, 80 ± 00, and 80 ± 00. Viability 96 ± 02, 94 ± 04, 95 ± 73, and 91 ± 75. Semen pH 8 ± 05, 8 ± 00, 8 ± 05 and 8 ± 00. Statistical analysis showed that the treatment had a significant effect on the viability of native chicken spermatozoa. It was concluded that domestic chicken spermatozoa could survive for 6 hours in a storage media ColdBox containing ice cubes.